Recommendations for reporting ion mobility Mass Spectrometry measurements. Issue 3 (1st February 2019) - Gabelica, Valérie; Shvartsburg, Alexandre A.; Afonso, Carlos; Barran, Perdita; Benesch, Justin L.P.; Bleiholder, Christian; Bowers, Michael T.; Bilbao, Aivett; Bush, Matthew F.; Campbell, J. Larry; Campuzano, Iain D.G.; Causon, Tim; et al.
Abstract : Here we present a guide to ion mobility mass spectrometry experiments, which covers both linear and nonlinear methods: what is measured, how the measurements are done, and how to report the results, including the uncertainties of mobility and collision cross section values. The guide aims to clarify some possibly confusing concepts, and the reporting recommendations should help researchers, authors and reviewers to contribute comprehensive reports, so that the ion mobility data can be reused more confidently. Starting from the concept of the definition of the measurand, we emphasize that (i) mobility values ( K 0 ) depend intrinsically on ion structure, the nature of the bath gas, temperature, and E / N ; (ii) ion mobility does not measure molecular surfaces directly, but collision cross section (CCS) values are derived from mobility values using a physical model; (iii) methods relying on calibration are empirical (and thus may provide method‐dependent results) only if the gas nature, temperature or E / N cannot match those of the primary method. Our analysis highlights the urgency of a community effort toward establishing primary standards and reference materials for ion mobility, and provides recommendations to do so. © 2019 The Authors. Mass Spectrometry Reviews Published by Wiley Periodicals, Inc.